Degradation of deproteinized natural rubber by Gordonia sp. isolated from enrichment consortia - Huong, Nguyen Lan; Thanh, Nguyen Thi; Dung, Nguyen Hoan; Trang, Nguyen Thi Thu; Quynh, Pham Thi (Vietnam Journal of Science and Technology, 2020)
Biodegradation is a potential way of decomposing deproteinized natural rubber (DPNR). The enrichment consortia were demonstrated from a rubber processing factor waste. Nine DPNR-degrading bacteria were isolated from those consortia. The highest DPNR film weight loss in a mineral salt medium (MSM) was 43.92 ± 2.30 % after 30 days incubation using strain 5A1. The formation of aldehyde group during rubber degradation of 5A1 was determined using Schiff staining and Fourier Transform Infrared spectroscopy (FTIR) analysis. The 16S rRNA gene sequence, of 5A1 showed the highest identity with that of Gordonia soli CC-AB07. This is the first report to demonstrate a strong ability to degrade DPNR by Gordonia sp.